1995
DOI: 10.1007/bf00193714
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a chimeric gene encoding an oryzacystatin-β-glucuronidase fusion protein into rice protoplasts and regeneration of transformed plants

Abstract: In order to construct transgenic rice plant with an introduced oryzacystatin (OC)-β-glucuronidase (GUS) fusion gene, we first introduced it into rice protoplasts by electroporation, together with a marker gene conferring hygromycinresistance (pUC-HPH). In a transient assay using the transfected protoplasts, both OC and GUS activities were detected. The GUS activity was higher when the OC-GUS fusion protein was expressed than when only a single GUS protein was expressed. Next, to isolate stable transformants, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In practice, the addition of any fusion partner to the primary structure of a proteinase inhibitor to increase its biological activity may be useful as long as its inhibitory efficiency is not altered negatively. Previous studies suggested a functional stability of the model cystatin, OCI, after fusion partners such as GST or β-glucuronidase were fused at its C or N termini (Michaud et al, 1994;Hosoyama et al, 1995;Tudyka and Skerra, 1997). In line with these observations, the data presented here, using tomato CDI as a fusion partner, strongly suggest that plant cystatins such as OCI or CCII may retain full inhibitory activity against insect cysteine proteinases when a fusion partner is attached at the N terminus.…”
Section: September 2005supporting
confidence: 88%
“…In practice, the addition of any fusion partner to the primary structure of a proteinase inhibitor to increase its biological activity may be useful as long as its inhibitory efficiency is not altered negatively. Previous studies suggested a functional stability of the model cystatin, OCI, after fusion partners such as GST or β-glucuronidase were fused at its C or N termini (Michaud et al, 1994;Hosoyama et al, 1995;Tudyka and Skerra, 1997). In line with these observations, the data presented here, using tomato CDI as a fusion partner, strongly suggest that plant cystatins such as OCI or CCII may retain full inhibitory activity against insect cysteine proteinases when a fusion partner is attached at the N terminus.…”
Section: September 2005supporting
confidence: 88%
“…1987b). However, we need further experimentation to confum in a final manner the safety of the transgenic rice whose cystatin content has been enriched artificially (Hosoyama et al 1994;Irie et al 1996).…”
Section: Insect Resistancementioning
confidence: 99%
“…Plant transformation is an effective method for obtaining crop plants protected from their pests and diseases, Therefore, we have attempted the introduction of the OC gene and its overexpression in the resultant transgenic rice plants [12,13]. However, the level of expression of the introduced OC gene was still insufficient for the effective protection against insect pests.…”
Section: Introductionmentioning
confidence: 99%